Influence of body mass index and age on day-of-surgery discharge, prolonged admission, and 90-day readmission after fast-track uni- compartmental knee arthroplasty - Jensen , Christian Bredgaard; Troelsen, Anders; Petersen, Pelle Baggesgaard; Jørgensen, Christoffer Calov; Kehlet, Henrik; Gromov, Kirill; Group, The Centre for Fast- Track Hip and Knee Replacement Collaborative (Acta Orthopaedica, 2021)
Background and purpose — The indications for unicompartmental knee arthroplasty (UKA) have become less restrictive and, today, high age and high BMI are not considered contraindications by many surgeons. While the influence of these patient characteristics on total knee arthroplasty is well documented, evidence on UKA is lacking. We investigated the effect of BMI and age on day of surgery (DOS) discharge, prolonged admission, and 90-day readmission following UKA surgery. Patients and methods — This retrospective cohort study included 3,897 UKA patients operated on between 2010 and 2018 in 8 fast-track arthroplasty centers. Patients were divided into 5 BMI groups and 5 age groups. Differences between groups in the occurrence of DOS discharge, prolonged admission > 2 days, and 90-day readmission was investigated using a chi-square test and mixed-effect models adjusted for patient characteristics using surgical center as a random effect. Results — Median LOS was 1 day. DOS discharge was achieved in 26% of patients with no statistically significant differences between BMI groups. DOS discharge was less likely in UKA patients aged > 70 years (age 71–80; odds ratio [OR] 0.7 [95% CI 0.6–0.9]). Prolonged admission was not affected by BMI or age in the adjusted analysis. 90-day readmission was more likely in patients with BMI > 35 (OR 1.9 [CI 1.1–3.1]) and patients aged 71–80 (OR 1.5 [CI 1.1–2.1]). Interpretation — Age > 70 years decreased the likelihood of DOS discharge after UKA. High BMI as well as advanced age increased the likelihood of 90-day readmis- sion. This should be noted by surgeons operating on patients with high BMI and age.